Study of Biodegradation and Bioremediation - Kaczorek, Ewa; Smułek, Wojciech (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Despite many years of efforts to reduce the emission of toxic pollutants into the environment, the contamination of air, soils and water by heavy metals and organic xenobiotics is still a serious problem. This has urged many scientists around the world to undertake research that aims to find effective methods of removing pollutants from the environment. Special attention is paid to biological methods, which, thanks to their numerous advantages, meet the expectations of the whole society. As part of the Special Issue "Study of Biodegradation and Bioremediation", in the MDPI journal Processes, several valuable articles have been published, which together form a picture of the current state of advanced research on the effective fight against environmental pollution. These include papers on the biodegradation of petroleum compounds or synthetic dyes by microorganisms or the enzymes they produce. In addition, the Special Issue includes papers on the bioremediation of dangerous heavy metals such as mercury and copper, and the results make a valuable contribution to our current state of knowledge on this topic. A separate and valuable part of this collection of publications are review articles devoted to the remediation of antineoplastic drugs, as well as the hopes and challenges connected with the application of nanotechnology in bioremediation. We are pleased that so many researchers from different parts of the world have submitted their articles on this topic. We are very grateful to them. We hope that readers of this collection will find many interesting ideas and relevant information that will lead to new solutions in the bioremediation and biodegradation of emerging environmental contaminants. Prof. Ewa Kaczorek Dr. Wojciech Smułek